Eksistensi Putusan Ultra Petita dalam Polemik Pengujian Mahkamah Konstitusi (MK) dalam Rangka Penegakan Hukum - Muhammad Saleh; AD Basniwati (Jatiswara, 2012)
As stipulated in the article 24 (1 and 2) of the constitution of Republic ofIndonesia 1945, Constitutional courts is, beside Supreme Court, one of the judicial courts element. This means that constitutional court is bound to general principles of judicial power, i.e. freedom, impartial and independent from any other institution in enforcing law and justice. One of the constitutional court’s decisions assumed to be controversy is what so called “ultra petita decision”. In the context of procedural law prevails in the court, ultra petita is decision which contains things out of claimant’s request within a judicial review process. This clearly will bring about legal discussion among legal experts.